PENGARUH MOTIVASI KERJA, LOYALITAS DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. ARISMA INDONESIA MERDEKA - Rr. Dimas Veronica Prihati; Futtry Nefridiany (STIE DWI SAKTI BATURAJA, 2020)
This research discusses work motivation, loyalty and work environment on employees’ performance at PT. Arisma Indonesia Merdeka. The population in this study was 43 employees at PT. Arisma Indonesia Merdeka. The analytical method used is a quantitative method by using the Multiple Linear Regression analysis tool that uses validity and reliability testing, and T test and F test. The results obtained in this study explain the value of t calculated work motivation (X1) is 4.143 greater Compared with t table value of 2.022 which means positive work motivation variables on employees’ performance, t loyalty count (X2) of 4.483 is greater than t table of 2.022 which means positive loyalty variables on employees’ performance and work environment t count (X3) of 3.242 is greater when compared with t table of 2.022, which means that the positive work environment variable on employees’ performance. While testing simultaneously (F Test) work motivation, loyalty and work environment variable, f count 33.919 is greater than the value of f table 2.85 which means work motivation, loyalty and work environment influence on the performance of employees of PT. Arisma Indonesia Merdeka.